2015
DOI: 10.1021/acsbiomaterials.5b00051
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized α-Helical Peptide Hydrogels for Neural Tissue Engineering

Abstract: Trauma to the central and peripheral nervous systems often lead to serious morbidity. Current surgical methods for repairing or replacing such damage have limitations. Tissue engineering offers a potential alternative. Here we show that functionalized α-helical-peptide hydrogels can be used to induce attachment, migration, proliferation and differentiation of murine embryonic neural stem cells (NSCs). Specifically, compared with undecorated gels, those functionalized with Arg-Gly-Asp-Ser (RGDS) peptides increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 74 publications
0
68
0
Order By: Relevance
“…This is not only due to the interesting nano-structures that are formed from the assembly of small molecules but also due to the fact that these supramolecular entities form functional hydrogels under suitable conditions. Gels are endowed with a variety of activities 9 including use as vehicles for drug delivery [10][11][12][13][14] , removal of pollutants and toxic metal ions from waste water [15][16][17][18] , tissue engineering [19][20][21] , making functional nano-hybrid systems [22][23][24] and biocatalysts [25][26][27] . There are many examples of functional hydrogel based on amino acids, peptides, carbohydrates and other biomolecules [28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…This is not only due to the interesting nano-structures that are formed from the assembly of small molecules but also due to the fact that these supramolecular entities form functional hydrogels under suitable conditions. Gels are endowed with a variety of activities 9 including use as vehicles for drug delivery [10][11][12][13][14] , removal of pollutants and toxic metal ions from waste water [15][16][17][18] , tissue engineering [19][20][21] , making functional nano-hybrid systems [22][23][24] and biocatalysts [25][26][27] . There are many examples of functional hydrogel based on amino acids, peptides, carbohydrates and other biomolecules [28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a RGD-functionalized α-helix-based hydrogel that combined two peptide sequences, hSAFp1 and hSAFp2, supported the proliferation and migration of murine embryonic neural stem cells. Moreover, signs of neuronal commitment were evidenced by the expression of the microtubule-associated protein-2 (MAP 2), the formation of neuritelike processes and electrophysiological signs (Mehrban et al, 2015).…”
Section: Synthetically Derived Hydrogels For Treatment Of Neuropathymentioning
confidence: 99%
“…Mehrban et al demonstrated that these fibrillar coiled-coils could be decorated with the RGDS cell-adhesive sequence. The resultant hydrogels could promote the growth, directional migration, and differentiation of murine embryonic neural stem cells in culture (Banwell et al 2009;Mehrban et al 2015).…”
Section: Coiled-coil Hydrogelsmentioning
confidence: 99%